11.2k views
5 votes
URGENT!!! Please answer ASAP with full working out thank you

URGENT!!! Please answer ASAP with full working out thank you-example-1
User Demo
by
4.9k points

1 Answer

5 votes

Explanation:


a) </p><p>\\ (a)/(x - 1) - (2)/(x + 1) = (4)/((x - 1)(x + 1)) \\ \\ (a(x + 1) - 2(x - 1))/((x - 1)(x + 1)) = (4)/((x - 1)(x + 1)) \\ \\ a(x + 1) - 2x + 2 = 4 \\ \\ a(x + 1) = 4 + 2x - 2 \\ \\ a(x + 1) = 2x + 2 \\ \\ a (x + 1) = 2(x + 1) \\ \\ a= (2(x + 1))/((x + 1)) \\ \\ \huge \red{ \boxed{a = 2}}

Solve b part yourself in the same way.

User SnowmanXL
by
5.6k points